Exploring the role of mitochondrial antiviral signaling protein in cardiac diseases - Qi, Yuying; Yin, Jie; Xia, Weiwei; Yang, Shiwei (Frontiers in Immunology, 2025)
Mitochondrial antiviral signaling (MAVS) was first discovered as an activator of NF-κB and IRF3 in response to viral infection in 2005. As a key innate immune adapter that acts as an ‘on/off’ switch in immune signaling against most RNA viruses. Upon interaction with RIG-I, MAVS aggregates to activate downstream signaling pathway. The MAVS gene, located on chromosome 20p13, encodes a 540-amino acid protein that located in the outer membrane of mitochondria. MAVS protein was ubiquitously expressed with higher levels in heart, skeletal muscle, liver, placenta and peripheral blood leukocytes. Recent studies have reported MAVS to be associated with various conditions including cancers, systemic lupus erythematosus, kidney disease, and cardiovascular disease. This article provides a comprehensive summary and description of MAVS research in cardiac disease, encompassing structure, expression, protein-protein interactions, modifications, as well as the role of MAVS in heart disease. It is aimed to establish a scientific foundation for the identification of potential therapeutic target.